It’s all in the eye of beholder - Maziarz, Mariusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The article aims at delivering a fresh look at the dependency of econometric results on research methods. The author discusses the Reinhart-Rogoff controversy and the literature on expansionary fiscal contractions with a view to argue that econometricians can obtain recalcitrant (inconsistent) results despite using similar datasets. Case studies are used to show the dependence of causal claims on econometric techniques. The choice of a weighting scheme or a method identifying the timing of historical contractions determines the obtained results. Considering the strong policy-orientation of the case studies, the article delivers evidence that economic policy-making is susceptible to the research methods used for the production of evidence. This study supports the conventionalist and constructivist stance in the philosophy of econometrics
Argumenta Oeconomica, 2019, Nr 2 (43), s. 307-328
Keywords: debt-to-GDP; expensionary fiscal contractions; economic methodology; constructivism; empirical macroeconomics; economic policy-making